Penerapan Teknik Outbound Untuk Meningkatkan Komunikasi Antar Pribadi Siswa - Sulkifly Sulkifly; Sitti Nurkia (PEDAGOGIKA, 2020)
This study aims: To determine the implementation, an overview of interpersonal communication students before and after given Outbound techniques, and to find out the application of outbound techniques can improve interpersonal communication students in SMA Negeri 1 Enrekang. This research uses a quantitative approach with a Pre Experimental Design model. Data collection using a questionnaire and observation. Data analysis uses descriptive statistical analysis and inferential statistical analysis. The results showed that: (1) The implementation of outbound techniques to improve interpersonal communication of students at SMA Negeri 1 Enrekang was carried out with three games namely moving glass, chain messages, and beautiful images according to the scenario. (2) The level of interpersonal communication of students before being given outbound techniques is in the low category then increasing after being given outbound techniques that is in the medium and high categories. (3) Application of outbound techniques can improve student interpersonal communication at SMA Negeri 1 Enrekang.